Developing the athlete. An applied sport science roadmap for optimizing performance - Kraemer, W. J.; Ratamess, N. A.; Newman, T. H. (Human Kinetics, 2025)
Over the past decade, the complexity of athlete development has increased, and sport science has become enthralled with metrics and genetics. While an abundance of information has emerged, there is still a lack of practical guidance on how to integrate this information with training to help athletes achieve their potential. Developing the Athlete: An Applied Sport Science Roadmap for Optimizing Performance brings much-needed clarity, providing a proven blueprint for bringing together the many fields related to sport science via an athlete development team that navigates the day-to-day development of each athlete.